Caloric restriction and aerobic exercise in sarcopenic and non‐sarcopenic obese women: an observational and retrospective study. Issue 3 (15th October 2015) - Barbat‐Artigas, Sébastien; Garnier, Sophie; Joffroy, Sandra; Riesco, Éléonor; Sanguignol, Frédéric; Vellas, Bruno; Rolland, Yves; Andrieu, Sandrine; Aubertin‐Leheudre, Mylène; Mauriège, Pascale
Abstract: Background: Sarcopenic obese (SO) individuals are a unique subset of subjects that combines obesity and sarcopenia. Traditional weight loss programmes including aerobic exercises may worsen their condition by further reducing their lean mass. The objective of this observational and retrospective study was to verify the effect of a mixed weight loss programme combining caloric restriction and exercise on body composition, and lipid‐lipoprotein profile of obese women according to their sarcopenic status. Methods: One hundred and forty‐six obese women (body mass index ≥ 30 kg/m 2 and fat mass ≥ 40%) participated to the 3 week usual and institutionalized weight‐reducing programme combining a dietary plan (1400 ± 200 kcal/day) and aerobic exercise (1 h/day, 6 days/week) of a specialized medical institution. The lean body mass index (LMI; lean mass/height 2 ) was calculated, and women in the lowest tertile of LMI were considered SO. Results: At baseline, SO women were older, and their body weight and LMI were lower than non‐sarcopenic obese (N‐SO) women ( p < 0.05). N‐SO and SO women similarly lost fat mass and improved their lipid‐lipoprotein profile ( p < 0.05), while differences in LMI between groups persisted at the end of the weight‐reducing programme. Indeed, N‐SO women lost lean mass ( p < 0.05) while SO did not. Conclusions: These findings suggest that a short weight loss programme combining caloric restriction and aerobic exercise may significantly reduce fat mass and improve lipid‐lipoprotein profile in obese women, independently of their sarcopenic status. Such programmes may have deleterious effects on lean mass in N‐SO subjects, only.